Branding and Digital Touchpoints as the Competitive Edge for the Service Firms in the Omnichannel Environment - Su, Wei Wen (2021)
Financial services industry has been one of the towards the global economy. Many their business communications and The usage of digital banking in the adoption by consumers. vital industries that contributed financial institutions have started to digitalize operations with the advancement of technology. in Asia Pacific region has observed increase of trend Malaysia is one of the countries which has joined the race of digitalization even though still falling behind the regional peers. The lead regulatory of financial instituti ons of Malaysia, Bank Negara Malaysia (BNM) has made the decision to issue five digital bank licenses in the first quarter of 2022 which has shown the initiative to prepare financial services industry in the country for digital disruption. Hence, the main objective of this research is to determine the relationship of digital touchpoints namely functional touchpoints, social touchpoints and community touchpoints on brand image towards customers’ loyalty intention in the financial services ind ustry in Malaysia. A quantitative study was conducted on 300 respondents who are above 18 years old and has experience with financial service providers in Malaysia. The questionnaires were distributed online to the respondents using the nonprobability (co nvenience) sampling method. Statistical Package for the Social Sciences (SPSS) version 22 was used to test the hypothesised relationships for this research. The findings revealed that all digital touchpoints have positive direct effect on brand image towar ds customers’ loyalty intention. Therefore, this research suggested that service firms should put more focus on planning and implementing digital touchpoints that can enhance the brand image and subsequently customers’ loyalty intention. Last but not least outcome of this research aims to provide beneficial insights , the on the branding and digital touchpoints impact towards customer loyalty from theoretical and practical perspective.